2012
DOI: 10.1097/ijg.0b013e31820d7e9d
|View full text |Cite
|
Sign up to set email alerts
|

Macular Retinal Ganglion Cell Complex Damage in the Apparently Normal Visual Field of Glaucomatous Eyes With Hemifield Defects

Abstract: In addition to ppRNFL thickness, the mGCC thickness could be a structural parameter for detecting preperimetric glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 36 publications
(37 reference statements)
4
49
0
1
Order By: Relevance
“…In agreement with our current findings, Takagi et al [23] recently compared the thicknesses of the mGCC and cRNFL in the apparently normal VF of glaucomatous eyes with hemifield defects with thicknesses in normal eyes using RTVue-100 SD-OCT. They reported that the thickness of the mGCC in the normal hemifield of the glaucomatous eyes was significantly less than in normal eyes (p<0.001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with our current findings, Takagi et al [23] recently compared the thicknesses of the mGCC and cRNFL in the apparently normal VF of glaucomatous eyes with hemifield defects with thicknesses in normal eyes using RTVue-100 SD-OCT. They reported that the thickness of the mGCC in the normal hemifield of the glaucomatous eyes was significantly less than in normal eyes (p<0.001).…”
Section: Discussionsupporting
confidence: 91%
“…Other studies using SD-OCT have also shown significant correlations between HFA retinal sensitivity and cRNFL or mGCC thickness in segments with and without VF defects [23,29]. Takagi et al [23] demonstrated that the thicknesses of the mGCC and cRNFL in the normal hemisphere of the glaucomatous eyes were significantly correlated with the total deviation in the VF parameters of the corresponding area, which suggested the presence of a diffuse loss in those glaucomatous eyes with localized hemifield defects.…”
Section: Discussionmentioning
confidence: 96%
“…Takagi et al [25] reported that macular GCC thickness decreased in the apparently normal hemisphere in glaucomatous eyes compared to the corresponding hemisphere in normal eyes. However, they also reported that there was no significant difference in macular thickness between apparently normal hemispheres of glaucomatous and normal eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Use of novel structural tests may improve clinical diagnosis, since for early glaucomatous visual field damage to be detected approximately 30 % of the retinal ganglion cells need to be lost [1]. Retinal nerve fiber layer (RNFL) thickness parameters of Fourier-domain (FD) optical coherence tomography (OCT) are believed to have diagnostic accuracy [2][3][4][5][6][7][8]; however, inner macular thickness parameters, which comprise tissue layers directly influenced by glaucomatous ganglion cell loss, show comparable or even higher diagnostic accuracy, particularly in detection of very early glaucoma, and in myopic eyes [9][10][11][12][13][14][15]. The RTVue-100 OCT (Optovue Inc., Fremont, CA, USA) is a new FD OCT systems.…”
Section: Introductionmentioning
confidence: 99%